Scaphoid fracture non-union: a systematic review of the arthroscopic management - Basso, Morena Anna; Smeraglia, Francesco; Ocampos-Hernandez, Montserrat; Balato, Giovanni; Bernasconi, Alessio; Corella-Montoya, Fernando (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: There is no consensus regarding the most appropriate treatment of scaphoid nonunion. This systematic review aimed to investigate whether wrist arthroscopy exerts a positive influence on bone union and clinical outcomes.Methods: We searched the literature on Medline (PubMed), Web of Science, Embase and Scopus databases using the combined keywords “scaphoid” AND “arthroscopy” AND “pseudoarthrosis” OR “nonunion”. Eighteen studies were finally included in our review. The quality of the studies was assessed using the Coleman Methodological Score.Results: Our systematic review has shown that arthroscopic management of scaphoid nonunion achieves a high rate of union and satisfactory clinical outcomes with minimal complications.Conclusions: There is need to perform randomized controlled trials reporting on the use of arthroscopy. In addition, the different pattern of pseudoarthrosis should be better classified to manage the patients who will benefit after the management.